Aplikasi Pembelajaran Sejarah Masjid Saka Tunggal Cikakak Kecamatan Wangon Kabupaten Banyumas Berbasis Mobile - Sayekthi, Mira; Azrino Gustalika, Muhammad; Dwi Alika, Shintia (Jurnal Tata Kelola dan Kerangka Kerja Teknologi Informasi, 2022)
Saka Tunggal Mosque is one of the oldest mosques located in Cikakak Village, Wangon District, Banyumas Regency. Based on the questionnaire distribution of tourists visiting the Saka Tunggal Mosque, 73.3% had difficulty finding information about the Saka Tunggal Mosque. One way to make it easier for tourists to find information about the Saka Tunggal Mosque is through the creation of an android-based Saka Tunggal Mosque learning application. The method used in making the Saka Tunggal Mosque application is the Multimedia Development Life Cycle (MDLC) because this method has stages that are suitable for use in making learning applications and have more detailed and clear stages. The application that has been made is then tested using the Black Box Testing method to find out whether the application is functionally running well. The data used in this study were obtained from the results of a questionnaire using Likert scale coding. Of the 50 questionnaire data obtained a significance value of 5% or 0.195 where the value obtained from the questionnaire is greater than the significance value. While the Cronbach's Alpha value on 17 questions obtained a result of 0.787 > 0.60, declared reliable.